Human-centred design thinking: a novel tool for co-creation in physical activity research - Rivera, Elise; Romero, Vivian; Maddison, Ralph (Health research policy and systems, 2025)
Despite the substantial health benefits of physical activity across the lifespan, most youth and adults are insufficiently physically active. To combat this trend, numerous policies and interventions have been developed, many of which have had modest effects. The limited effectiveness of such interventions has been linked to the lack of or minimal community involvement. Consequently, there have been calls for solutions with greater community buy-in. In particular, there has been a rise in the use of co-creation in physical activity research, where stakeholders are engaged in understanding and defining problems and designing localised and contextual solutions. While there are many benefits to co-creation (for example, collaboration and empowerment), there are also challenges, including the underreporting of co-creation approaches and methodologies used in physical activity research. We argue that human-centred design thinking can be a tool for approaching, complementing, and elevating co-creation. We discuss human-centred design thinking and offer strengths for how it can augment co-creation, such as through the Double Diamond model, toolkits and field guides, established activities, reporting guideline’s and asking different questions to spark social innovation. We also present a case study to showcase how human-centred design thinking as an approach to co-creation can look.